Failure to Validate a Multivariable Clinical Prediction Model to Identify Pediatric Intensive Care Unit Patients at High Risk for Candidemia. (29th April 2015) - Fisher, Brian T.; Ross, Rachael K.; Roilides, Emmanuel; Palazzi, Debra L.; Abzug, Mark J.; Hoffman, Jill A.; Berman, David M.; Prasad, Priya A.; Localio, A. Russell; Steinbach, William J.; Vogiatzi, Lambrini; Dutta, Ankhi; et al.
Abstract: We attempted to validate a previously derived clinical prediction rule for candidemia in the pediatric intensive care unit. This multicenter case control study did not identify significant association of candidemia with most of the previously identified predictors. Additional study in larger cohorts with other predictor variables is needed.